PENGARUH CAUSE RELATED MARKETING, CORPORATE IMAGE, DAN BRAND ATTRACTIVENESS TERHADAP CONSUMER PURCHASE DECISION PRODUK THE BODY SHOP DI JAKARTA BARAT - JEREMI KORAYAN; WIBISONO SOEDIONO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to know how the influence of cause related marketing, corporate image, and brand attractiveness to consumer purchase decision product of The Body Shop at West Jakarta. The research design used in descriptive research and causality research. The sampling used in this research is nonprobability sampling by purposive sampling methods and will require 100 respondents. The respondents are considered as consumer that are purchasing the products of The Body Shop by using their own incomes. The total of entry data was analyzed using multiple regression. The result have shown that there are influence among cause related marketing, corporate image and brand attractiveness with consumer purchase decision product of The Body Shop at West Jakarta.